Duodenal carcinoma in MUTYH-associated polyposis. Issue 11 (30th August 2006) - Nielsen, M; Poley, J W; Verhoef, S; van Puijenbroek, M; Weiss, M M; Burger, G T; Dommering, C J; Vasen, H F A; Kuipers, E J; Wagner, A; Morreau, H; Hes, F J
Abstract : Bi-allelic germline mutations in the MUTYH gene give rise to multiple adenomas and an increased incidence of colorectal cancer. In addition, duodenal adenomas and other extra-colonic manifestations have been described in MUTYH-associated polyposis (MAP) patients. We describe two patients with bi-allelic MUTYH gene mutations with duodenal carcinoma. The tumour in Patient A was detected during evaluation of non-specific abdominal complaints. Patient B was already diagnosed with tens of adenomas and a colon carcinoma, when a duodenal neoplasm was detected. The identification of somatic G>T mutations in codon 12 of the K-RAS2 gene provides evidence that the duodenal lesions were induced by MUTYH deficiency. Studies in larger series of MAP patients are needed to investigate the risk of upper-gastro-intestinal malignancies and to determine further guidelines for endoscopical surveillance.